The relationship between cognitive and affective control and adolescent mental health - Savannah Minihan; Levi Kumle; Kate Maston; Debopriyo Bal; Aliza Werner‐Seidler; Helen Christensen; Susanne Schweizer (Wiley, 2024)
Abstract Background Cognitive control problems have been implicated in the etiology and maintenance of mental health problems, including depression, in adults. Studies in adolescents have been more equivocal, with some showing changes in cognitive control in adolescents with mental health problems, whereas others fail to show an association. This study examines whether adolescent mental health is associated with affective control, the application of cognitive control in affective contexts, which shows more protracted development than cognitive control. Methods The present study investigated the association of cognitive and affective control with depressive symptomatology and self‐reported diagnostic history of mental health problems in adolescents. The study included 1929 participants (Mage = 13.89) from the Future Proofing Study (N = 6,388, 11-16 years), who completed affective (incl., affective stimuli) and/or cognitive (incl., neutral stimuli) versions of a working memory (backward digit‐span) and/or shifting (card‐sorting) task at least once within 3 weeks of assessing mental health. Results Poorer working memory was associated with greater depressive symptomatology in adolescents (β = −0.06, p = .004), similarly across cognitive and affective control conditions (β = −0.02, p = .269). Adolescents with self‐reported diagnostic history of mental health problems had significantly poorer shifting ability in affective compared to cognitive control conditions (b = 0.05, p = .010), whereas for adolescents with no self‐reported diagnoses, shifting ability did not differ between conditions (b = −0.00, p = .649). Conclusions The present analyses suggest that working memory difficulties, in particular, may be associated with the experience of current depressed mood in adolescents. Problems with affective shifting may be implicated in a range of mental health problems in adolescents. Given the ubiquitous need for efficient cognitive functioning in daily life, enhancing cognitive and affective control in adolescents may be a promising means of improving functioning across a range of domains, including affective functioning, and by extension, adolescent mental health.